CGIAR's Agriculture Breakthrough 2023 Launch Event - CGIAR (CGIAR System Organization, 2023)
This was a webinar for the launch of CGIAR led Breakthrough Report, with high profile speakers including Ban ki Moon and Minister from New Zealand.